High functionality reversible arithmetic logic unit - Shaveta Thakral; Dipali Bansal (Institute of Advanced Engineering and Science, 2020)
Energy loss is a big challenge in digital logic design primarily due to impending end of Moore’s Law. Increase in power dissipation not only affects portability but also overall life span of a device. Many applications cannot afford this loss. Therefore, future computing will rely on reversible logic for implementation of power efficient and compact circuits. Arithmetic and logic unit (ALU) is a fundamental component of all processors and designing it with reversible logic is tedious. The various ALU designs using reversible logic gates exist in literature but operations performed by them are limited. The main aim of this paper is to propose a new design of reversible ALU and enhance number of operations in it. This paper critically analyzes proposed ALU with existing designs and demonstrates increase in functionality with 56% reduction in gates, 17 % reduction in garbage lines, 92 % reduction in ancillary lines and 53 % reduction in quantum cost. The proposed ALU design is coded in Verilog HDL, synthesized and simulated using EDA (Electronic Design Automation) tool-Xilinx ISE design suit 14.2. RCViewer+ tool has been used to validate quantum cost of proposed design.